PELAKSANAAN PROGRAM KESELAMATAN KESEHATAN KERJA (K3) DALAM RANGKA MENGURANGI KECELAKAAN KARYAWAN (Kasus Bagian Teknik dan Distribusi PT. PLN Ranting Bangkinang) - Erfa, Ronesha Tria Maharita; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
PT . PLN ( Persero ) Branch Bangkinang is a company engaged inelectricity that serves as executor and services that serve as a means of electricalservices and electrical facilities in Kampar regency . Electricity is needed by thecommunity because all electricity is one of the requirements that must be met ,because the electricity can meet the needs for companies or industries are growing,especially in Kampar district .Based on field prasurvey in the implementation of employee safety healthand Techniques section Disribusi PT . PLN ( Persero ) Branch Bangkinang are : (a) the lack of socialization periodically from PLN employees to apply K3 , ( b ) Thehead of PLN less assertive in pursuing technical staff in using the tools to do thejob safety and engineering parts distribution , ( c ) there are still some employeeswho do not use the equipment in accordance with procedures , ( d ) lack ofknowledge held by employees of the engineering and food distribution PT . PLN (Persero ) Bangkinang Ranting about things that can cause workplace accidents orlalainya employees in the use of high voltage gloves and other safety equipment .The purpose of this study is to investigate and analyze the implementationof the Occupational Health Safety ( K3 ) Mechanical Parts employees anddistribution PT . PLN ( Persero ) Branch Bangkinang and to identify and analyzethe barriers in the implementation of the Occupational Health Safety ( K3 )Mechanical Parts employees and distribution PT . PLN ( Persero ) BranchBangkinang .Keyword : Health Safety Program (K3 ) , Reducing Employee Accidents , SafeWorking Conditions